The evaluation of the prospects for the application of mass-spectrometric analysis of the amplified DNA fragments for the purpose of forensic medical expertise - Leonov, S N; Zemskova, E Iu; Timoshenko, T V; Ivanov, P L (Sudebno-meditsinskaia ekspertiza, 2014)
The objective of the present study was to evaluate the prospects for the application of the mass-spectrometric analysis for the solution of the problems facing modern forensic-medical genetics as illustrated by the example of the new experimental multiplex approach to the typing of human DNA with the use of the complex PLEX-ID platform. The validation study involved all stages of the processing chain. The results of the study were used to develop the recommendations for the optimization of the analytical system being used. The comparative analysis of the experimental PLEX-ID technology and the traditional electrophoretic system for the analysis of polymorphism of amplified DNA fragments has demonstrated the potential advantages of the mass-spectrometric technique, such as the enhanced informative value of the forensic expert evaluation of polymorphism of STR-loci due to the possibility of identifying SNP and extension in them and therefore their allelic spectrum.